Intet nyt under solen? Refleksion over feministisk teori - Rosenbeck, Bente (Kvinder, Køn & Forskning, 1997)
The article deals with the revival of Jürgen Habermas and critical theory in the debate of feminist theory and method. At the conceptual level the relationship between discourse and identity and the question of a non-discoursive concept of experience are discussed. Several feminist researchers who have been attracted by poststructuralist thinking now aim at a combination of Habermas and Foucault. (e.g. Lois McNay). Also Seyla Benhabib and her critical  questions about postmodernism and emancipation enjoy great prominence. Can feminist theory be postmodernist and still retain an interest in emancipation? The article encourages to consider the possible combination of Foucalt's critique of institutions and of power/knowledge with the utopian thinking of Habermas.